Monasticism of Byzantine Africa in Narrative Sources - Urbaniec, Arkadiusz (Vox Patrum, 2026)
The object of the present article is to collect and analyse passages from narrative sources concerning monasticism in the Byzantine prefecture of Africa in the sixth to seventh centuries, in an attempt to determine the nature and extent of the monastic movement in the area. Due to the fragmentary nature of the surviving source base and its concentration around events of a political nature and relating to Christological controversies, the narrative texts (including the works of Procopius of Caesarea, the chronicle of Victor of Tonnona, and hagiographic literature) were also confronted with epistolographic and normative material, allowing for a more complete picture of the subject under study. The analysis has shown that there is no apparent continuity in the existence of monastic foundations between the Late Roman period, Vandal rule and Byzantine times; moreover, the information appearing in the sixth and seventh centuries basically concerns only monasteries and monks active in the area of Africa Proconsularis. The largest amount of data is provided by the Greek sources, which refer mainly to the situation in the first half of the seventh century and the Monothelite controversy, showing Africa as a place of settlement for numerous Eastern monks, but without mentioning the Latin-speaking monastic structures that had existed there before. The picture obtainable from the narrative of Byzantine monasticism in the area is therefore fragmentary and in many places hypothetical.